2019
DOI: 10.1111/jpi.12555
|View full text |Cite
|
Sign up to set email alerts
|

Is circadian rhythmicity a prerequisite to coma recovery? Circadian recovery concomitant to cognitive improvement in two comatose patients

Abstract: Circadian rhythmicity (CR) is involved in the regulation of all integrated functions, from sleep‐wake cycle regulation to metabolic function, mood and cognition. However, the interdependence of CR, cognition and consciousness has been poorly addressed. To clarify the state of CR in coma and to determine the chronological relationship between its recovery and consciousness after brain lesions, we conducted a longitudinal observational study investigating how the state of CR was chronologically related with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Historically, Nowak et al stated that both salivary and urinary melatonin measurement methods were strongly correlated with serum concentrations, and would be useful as non-invasive tests for melatonin concentration [66]. More recently in 2020, Rzepka-Migut and Paprocka detailed melatonin measurement considerations in an extensive systematic review, supporting this concept [67]. They found that urinary and salivary melatonin were useful for assessing serum concentrations non-invasively; however, there are a few caveats that must be considered when collecting these data [67].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Historically, Nowak et al stated that both salivary and urinary melatonin measurement methods were strongly correlated with serum concentrations, and would be useful as non-invasive tests for melatonin concentration [66]. More recently in 2020, Rzepka-Migut and Paprocka detailed melatonin measurement considerations in an extensive systematic review, supporting this concept [67]. They found that urinary and salivary melatonin were useful for assessing serum concentrations non-invasively; however, there are a few caveats that must be considered when collecting these data [67].…”
Section: Discussionmentioning
confidence: 99%
“…More recently in 2020, Rzepka-Migut and Paprocka detailed melatonin measurement considerations in an extensive systematic review, supporting this concept [67]. They found that urinary and salivary melatonin were useful for assessing serum concentrations non-invasively; however, there are a few caveats that must be considered when collecting these data [67]. For urinary collection, liver and kidney function must be considered as melatonin is metabolized in the liver and excreted via urine [67].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations